Using Resources: Conceptualizing the Mediation and Reflective Use of Tools and Signs - Gillespie, Alex; Zittoun, Tania (My University, 2010)
The idea that culture comprises resources that are used has become a popular means to re-conceptualize the culture—agency antinomy. However, the theorization of using resources is fragmented. The present article reviews several attempts to theorize resources, arguing that there has been too much focus upon the resources themselves, while the notion of use has been neglected. Focusing upon mode of use, as opposed to the resources used, the article underscores the importance of distinguishing between tools, which are used to act upon the world, and signs, which are used to act upon the mind. The article also argues for a distinction between non-reflective use, or mediation, and reflective use of resources. Future research should focus upon the transformation of tools into signs and the transformation of mediation into reflective use. The article concludes by discussing problematic issues that remain in conceptualizing the use of resources.
Keywords: mediation; reflection; resources; signs; tools; use